Electron microscopic tomography reveals discrete transcleft elements at excitatory and inhibitory synapses - High, Brigit; Cole, Andy A.; Chen, Xiaobing; Reese, Thomas S. (Frontiers in Synaptic Neuroscience, 2015)
Electron microscopy has revealed an abundance of material in the clefts of synapses in the mammalian brain, and the biochemical and functional characteristics of proteins occupying synaptic clefts are well documented. However, the detailed spatial organization of the proteins in the synaptic clefts remains unclear. Electron microscope tomography provides a way to delineate and map the proteins spanning the synaptic cleft because freeze substitution preserves molecular details with sufficient contrast to visualize individual cleft proteins. Segmentation and rendering of electron dense material connected across the cleft reveals discrete structural elements that are readily classified into five types at excitatory synapses and four types at inhibitory synapses. Some transcleft elements resemble shapes and sizes of known proteins and could represent single dimers traversing the cleft. Some of the types of cleft elements at inhibitory synapses roughly matched the structure and proportional frequency of cleft elements at excitatory synapses, but the patterns of deployments in the cleft are quite different. Transcleft elements at excitatory synapses were often evenly dispersed in clefts of uniform (18 nm) width but some types show preference for the center or edges of the cleft. Transcleft elements at inhibitory synapses typically were confined to a peripheral region of the cleft where it narrowed to only 6 nm wide. Transcleft elements in both excitatory and inhibitory synapses typically avoid places where synaptic vesicles attach to the presynaptic membrane. These results illustrate that elements spanning synaptic clefts at excitatory and inhibitory synapses consist of distinct structures arranged by type in a specific but different manner at excitatory and inhibitory synapses.